HUBUNGAN MOTIVASI BERPRESTASI DAN SIKAP BERKOMUNIKASI DENGAN PELAKSANAAN MANAJEMEN KELAS GURU - GURU SEKOLAH LANJUTAN TINGKAT PERTAMA NEGERI KECAMATAN BARUS DAN PEMEKARANNYA - SLAMET RIYADI (LP2MTBM MAKARIOZ, 2020)
This research aims to know the motivation relationship of achievement and attitude of communication to the implementationof class management conducted by the teacher. The study proposed three hypotheses. Firstly, there is a positive andsignificant relationship between the achievement motivation and the management of the first-class high school teachers inBarus sub-district and its developer. Secondly, there is a positive and significant relationship between the attitude ofcommunicating with the management of the class of first-level secondary school teachers in Barus sub-district and itspemekarannya. Thirdly, there is a positive and significant relationship between the achievement motivation and the attitudeof communicating together with the implementation of the class management of the first-level advanced school teachers inBarus subdistrict and its developer. The population of this research is the teachers of the first level of secondary school inBarus subdistrict and its 112 people. Sample withdrawal using stratified proportional ramdom sampling, with strata level ofeducation, rank/class and term of employment. The results showed that the motivation of achievement and the attitude ofcommunication and implementation of class management are categorized into sufficient categories. It was discovered thatthe motivation of achievement and the attitude of communicating either alone or jointly relates significantly to theimplementation of the class management teachers of the first level of secondary school in the district state of Barus and itsPemekarannya ; 0,662(40,96%); 0,863(74,5%) 2 12   y y r R . The findings of this research show that theimplementation of class management teachers of the first level of secondary school in the district of Barus and its conversioncan be predicted or determinated by the motivation of achievement and the attitude of communicating either individually ortogether.